Effect of supplements/intensive nutrition on pressure ulcer healing: a multicentre, randomised controlled study. (2nd May 2023) - Banks, Merrilyn D; Webster, Joan; Bauer, Judy; Dwyer, Kathleen; Pelecanos, Anita; MacDermott, Paula; Nevin, Amy; Coleman, Kerrie; Campbell, Jill; Hickling, Donna; Byrnes, Angela; Capra, Sandra
Abstract : Objective: To investigate the effectiveness of an intensive nutrition intervention or use of wound healing supplements compared with standard nutritional care in pressure ulcer (PU) healing in hospitalised patients. Method: Adult patients with a Stage II or greater PU and predicted length of stay (LOS) of at least seven days were eligible for inclusion in this pragmatic, multicentre, randomised controlled trial (RCT). Patients with a PU were randomised to receive either: standard nutritional care (n=46); intensive nutritional care delivered by a dietitian (n=42); or standard care plus provision of a wound healing nutritional formula (n=43). Relevant nutritional and PU parameters were collected at baseline and then weekly or until discharge. Results: Of the 546 patients screened, 131 were included in the study. Participant mean age was 66.1±16.9 years, 75 (57.2%) were male and 50 (38.5%) were malnourished at recruitment. Median length of stay was 14 (IQR: 7–25) days and 62 (46.7%) had ≥2 PUs at the time of recruitment. Median change from baseline to day 14 in PU area was –0.75cm 2 (IQR: –2.9_–0.03) and mean overall change in Pressure Ulcer Scale for Healing (PUSH) score was –2.9 (SD 3.2). Being in the nutrition intervention group was not a predictor of change in PUSH score, when adjusted for PU stage or location on recruitment (p=0.28); it was not a predictor of PU area at day 14, when adjusted for PU stage or area on recruitment (p=0.89) or PU stage and PUSH score on recruitment (p=0.91), nor a predictor of time to heal. Conclusion: This study failed to confirm a significant positive impact on PU healing of use of an intensive nutrition intervention or wound healing supplements in hospitalised patients. Further research that focuses on practical mechanisms to meet protein and energy requirements is needed to guide practice.